Toxic Relationship in Emerging Adulthood - Zein Permana; Koentjoro Koentjoro; Muhammad Najib Azca (Pusat Studi Wanita dan Keluarga UGM, 2023)
This study aims to explore the primary concerns of emerging adulthood in Bandung, Indonesia, and the psychological dynamics that occur in their lives during this stage. Using a three-phase approach, a survey was conducted among 1034 participants (mean age = 20.4) to identify their current concerns. A grounded approach was employed in the second phase to determine the recurring themes of concern. The findings indicate that the primary concern of emerging adults is related to potentially toxic romantic relationships. To gain a deeper understanding of the psychological dynamics associated with these relationships, in-depth interviews were conducted with 11 emerging adults who had experienced toxic relationships. The results revealed five critical areas within toxic relationships, including: 1) reasons for initiating the relationship; 2) the